Pengaruh Panjang Kolom Udara terhadap Tinggi Rendah Bunyi - Athalia Dimansyah; Nur Sufi Aulia; Nurul Hasanah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Sound is a longitudinal wave that propagates through a medium (solid, liquid, or gaseous substance). The height and frequency of the sound is affected by the length of the air column that the waves pass through. This study aims to analyze the relationship between the length of the air column and the frequency of sound through a simple experiment using straws and a glass filled with water. The research method used is descriptive and qualitative experimental methods. Descriptive analysis of experimental data can be used to describe the pattern of relationship between air column length and low noise height. By involving variations in the length of the air column by cutting the straw into several sizes (5 cm, 10 cm, 15 cm, and 20 cm), and other tools in the form of glasses, scissors, rulers, markers and water. Next, observe changes in sound frequency when blown without water and in water. The results show that the shorter the air column, the higher the frequency of sound (higher pitch) produced, and vice versa. that the length of the air column affects the low altitude of the sound directly.